Implementasi Pembelajaran Fisika Berbasis Lab Virtual Olabs Terhadap Hasil Belajar Mahasiswa - Sitinjak, Erni Kusrini; Sigiro, Mula; Pardede, Hebron; Silitonga, Suryani; Sijabat, Naomi Christine (Lembaga Riset dan Inovasi Almatani, 2025)
This study aims to analyze the effect of implementing Olabs virtual lab-based physics learning on learning outcomes, compare student learning outcomes using Olabs virtual labs with conventional methods, and identify the advantages and limitations of implementing Olabs virtual labs in physics learning. This study employed a quasi-experimental approach with a pretest-posttest control group design to evaluate the effect of Olabs virtual lab implementation on student learning outcomes in physics courses. Therefore, the instrument used in this study was a pretest-posttest. The study population was Physics Education student at HKBP Nommensen University. After administering different treatments to the two classes, the control and experimental classes, the average learning outcomes for the control class were 66.56 for the pretest and 75 for the posttest. Meanwhile, in the experimental class, the average pretest acore was 66.92 and the posttest acore was 85.38. the data analysis concluded that implementing Olabs virtual lab-based physiscs learning improved the learning outvomes of physics education students in the experimental class.